2020
DOI: 10.1088/1758-5090/ab782d
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite bioink exploits dynamic covalent bonds between nanoparticles and polysaccharides for precision bioprinting

Abstract: The field of bioprinting has made significant recent progress towards engineering tissues with increasing complexity and functionality. It remains challenging, however, to develop bioinks with optimal biocompatibility and good printing fidelity. Here, we demonstrate enhanced printability of a polymer-based bioink based on dynamic covalent linkages between nanoparticles (NPs) and polymers, which retains good biocompatibility. Amine-presenting silica NPs (ca. 45 nm) were added to a polymeric ink containing oxidi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 49 publications
3
31
0
Order By: Relevance
“…The reversible imine bonds between amines on the nanoparticles and aldehydes of oxidized alginate lead to significant enhancement of the rheological properties and better printability. The yield stress increased 5.4-fold without compromising the biocompatibility of the bioink when using 2 wt% nanoparticles [182]. Moreover, as stated before, it is preferable to avoid the use of cytotoxic crosslinkers or UV light, which can be damaging to the cells.…”
Section: Supramolecular Biopolymers For Bioprintingmentioning
confidence: 87%
“…The reversible imine bonds between amines on the nanoparticles and aldehydes of oxidized alginate lead to significant enhancement of the rheological properties and better printability. The yield stress increased 5.4-fold without compromising the biocompatibility of the bioink when using 2 wt% nanoparticles [182]. Moreover, as stated before, it is preferable to avoid the use of cytotoxic crosslinkers or UV light, which can be damaging to the cells.…”
Section: Supramolecular Biopolymers For Bioprintingmentioning
confidence: 87%
“…[290][291] The rheological properties of such nanocomposite bioinks can be manipulated to a great extent by controlling the size, concentration of nanoparticles, and more importantly the type of interactions between nanoparticles and polymers. [290][291] The function of these nanoparticles was to serve as a mechanical reinforcement and mechanism to dissipate mechanical energy. 240 Self-healing Bioinks: In an effort to reproduce the flow properties necessary for bioprinting, it is suggested that materials crosslinked with reversible bonds could rapidly self-heal and be a promising strategy for producing extrusion bioprinting materials (Figure 19).…”
Section: Figure 19 Common Strategies To Achieve Good Extrusion Printabilitymentioning
confidence: 99%
“…The formation of reversible imine bonds between amines on the nanoparticles and aldehydes of OxA provoked considerably enhanced rheological properties resulting in the generation of porous constructs and an ear structure with overhangs and high structural fidelity. The improvement was mostly due to electrostatic interactions between cationic SiNPs and anionic polysaccharides and was significantly impacted by the size and concentration of the nanoparticles as well as the length of polymer chains [ 62 ]. This study indicates that these interactions should be considered when bioprinting cartilage.…”
Section: Types Of Smart Bioinksmentioning
confidence: 99%